Full-semester and time-compressed fluency disorders course: an evaluation of student perceptions of competence, satisfaction, and workload - DeVeney, Shari L.; Teten, Amy F.; Friehe, Mary J. (Social Welfare: Interdisciplinary Approach, 2015)
This article addresses the effectiveness of a time-compressed four-week course format compared to a full-semester 16-week format for a graduate-level course.  Participants were 78 students enrolled in a speech-language pathology course, fluency disorders. No significant differences were noted for student competency self-perceptions.  However, time-compressed students reported significantly higher levels of course satisfaction and workload difficulty.
Keywords: fluency disorders; course format; time-compressed; full-semester; student perceptions; workload; course satisfaction